1993
DOI: 10.1136/gut.34.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Oesophagitis is as important as oesophageal stricture diameter in determining dysphagia.

Abstract: It is a common observation that stricture patients with severe dysphagia may have a wide lumen, while others with a narrow stricture have few swallowing complaints. In 64 patients with benign oesophageal stricture the dysphagia score (determined by questionnaire and by a test meal both based on nine different items of food scored according to their solidity) was compared with the diameter of the stricture measured radiologically by premeasured barium spheres. There was evidence of an association, but the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that esophageal inflammation can be associated with as much swallowing difficulty as frank luminal narrowing [7]. Vomiting and weight loss in association with dysphagia at presentation were significant predictors of malignancy.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that esophageal inflammation can be associated with as much swallowing difficulty as frank luminal narrowing [7]. Vomiting and weight loss in association with dysphagia at presentation were significant predictors of malignancy.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, no such relationship existed before fundoplication. Apparently, other factors contribute to dysphagia in patients with GERD, such as esophageal hypersensitivity to distention due to mucosal inflammation (30) or a lowered sensory threshold to bolus distention (31). Furthermore, incomplete esophageal emptying upon peristalsis might be another contributing parameter.…”
Section: Discussionmentioning
confidence: 99%
“…This system was associated with the diameter of the stricture at a rate of 30% and esophagitis and other factors at a rate of 70% (23). The dysphagia score displayed parallelism with the diameter of the stricture only in cases in which the esophageal lumen was shorter than 5 mm.…”
Section: Dietmentioning
confidence: 94%